Development of Mathematics Teaching Materials with Integration of 4C Skills For College Students - Ranti, Mayang Gadih; Saputri, Rinda Azmi (AlphaMath : Journal of Mathematics Education, 2025)
The development of 4C skills—critical thinking, creativity, collaboration, and communication—is essential for preparing college students to meet the demands of the 21st century. Despite this urgency, there remains a significant gap in the availability of mathematics teaching materials that explicitly integrate these skills. This study addresses that gap by developing a novel teaching module that embeds 4C skill development within mathematics instruction, specifically in a basic statistics course for college students. Employing a Research and Development (R&D) methodology, the module was designed, tested, revised, and finalized through five systematic stages. Product trials were conducted with third-semester students in the Mathematics Education Program at UIN Antasari Banjarmasin. Data were collected through tests, questionnaires, and interviews, and analyzed using both quantitative and qualitative methods. Results indicate that the developed module is highly valid, practical, and effective. The key contribution of this research lies in offering an innovative educational resource that not only enhances mathematical understanding but also actively cultivates students’ 4C skills. This integrated approach represents a novel contribution to mathematics education and provides a model for future curriculum development aimed at fostering essential 21st-century competencies